2019
DOI: 10.1007/s00595-019-01787-9
|View full text |Cite
|
Sign up to set email alerts
|

Daikenchuto accelerates the recovery from prolonged postoperative ileus after open abdominal surgery: a subgroup analysis of three randomized controlled trials

Abstract: Purpose Prolonged postoperative ileus (POI) is a common complication after open abdominal surgery (OAS). Daikenchuto (DKT), a traditional Japanese medicine that peripherally stimulates the neurogenic pathway, is used to treat prolonged POI in Japan. To analyze whether DKT accelerates the recovery from prolonged POI after OAS, we conducted a secondary analysis of three multicenter randomized controlled trials (RCTs). Methods A secondary analysis of the three RCTs support… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 27 publications
0
15
0
Order By: Relevance
“…However, after surgery, patients experience general dysfunction, such as bowel and physical dysfunction, due to the long surgical duration and large abdominal incisions. Among Kampo medicines, several investigators have reported that Daikenchuto (TJ-100) showed clinical efficacy after abdominal digestive surgery [10][11][12][13][14][15]. TJ-100 is a traditional Japanese medicine containing processed ginger, ginseng, and Zanthoxylum fruit.…”
Section: Clinical Effects Of Kampo Medicine For Postoperative Dysfuncmentioning
confidence: 99%
“…However, after surgery, patients experience general dysfunction, such as bowel and physical dysfunction, due to the long surgical duration and large abdominal incisions. Among Kampo medicines, several investigators have reported that Daikenchuto (TJ-100) showed clinical efficacy after abdominal digestive surgery [10][11][12][13][14][15]. TJ-100 is a traditional Japanese medicine containing processed ginger, ginseng, and Zanthoxylum fruit.…”
Section: Clinical Effects Of Kampo Medicine For Postoperative Dysfuncmentioning
confidence: 99%
“…A clinical pharmacology study has also revealed that DKT enhances small intestinal motility in healthy volunteers [14]. In addition, placebo-controlled DB-RCT for POI has also been shown to improve POI symptoms in patients with abdominal surgery [15,16]. In the United States, DKT has also been approved as an investigational drug by the Food and Drug Administration and is primarily used for the treatment of POI [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Many of these compounds have been used to treat a variety of diseases in clinical, even in CRC [7]. TU-100 (Daikenchuto) is a commonly prescribed Japanese herbal medicine that has been used to treat gastrointestinal motility and prevent post-operative intestinal dysfunction providing the most preclinical and clinical efficacy in several trials [8][9][10][11][12][13][14]. TU-100 is a mixture of herbal medicines such as processed ginger (Zingiberis Siccatum Rhizoma), ginseng (Ginseng radix), Japanese pepper (Zanthoxylum fruit), and maltose sugar by a weight ratio of 5.6%, 3.3%, 2.2%, 88.9%, respectively [10,15].…”
Section: Introductionmentioning
confidence: 99%